Nutraceutical-based telomerase inhibitors: Renewed hope for cancer therapy - Yasser Fakri Mustafa (Elsevier, 2024)
Background: : Attributes of potential targets for anticancer therapy are currently being investigated for telomeres, telomerase, and their combined complex. Study Design: Telomerase (TRTase) is a distinct reverse transcriptase that is thought to be the leader in almost all cancer-derived cells and is primarily in charge of controlling telomere (TLM) length. This enzyme therefore guarantees unabated cell division during carcinogenesis, a characteristic of cancer, and this distinguishing factor has made TRTase the spotlight target for pharmaceutical research in cancer therapy. The capacity of nutraceuticals to inhibit TRTase, impair TLMs, and hinder their complex formation offers a window of opportunity for the discovery of new cancer-treatment targets. Purpose: This review attempts to provide a fundamental understanding of TLM investigation, TRTase regulatory frameworks, and the diverse binding proteins that hinder the TLM-TRTase combined structure. Moreover, this study highlights nutraceuticals that address TLMs, inhibition at the molecular level, and inhibitors of the catalytic TRTase subunits. Conclusion: This thorough knowledge of TRTase's physiological action will offer crucial information for boosting the effectiveness of plausible chemotherapeutic drug designs.